Tidal inlets in the Anthropocene: Geomorphology and benthic habitats of the Chioggia inlet, Venice Lagoon (Italy). Issue 11 (18th June 2019) - Fogarin, Stefano; Madricardo, Fantina; Zaggia, Luca; Sigovini, Marco; Montereale‐Gavazzi, Giacomo; Kruss, Aleksandra; Lorenzetti, Giuliano; Manfé, Giorgia; Petrizzo, Antonio; Molinaroli, Emanuela; Trincardi, Fabio
Abstract : Within a multidisciplinary approach, we mapped with unprecedented detail the seafloor morphology, sediment distribution and benthic habitats of a tidal inlet which has been highly impacted by human activity. We identified an unusual habitat for lagoon environment connected to rip‐rap used for jetties and hard structures and we estimated that the new pattern of flow around these hard structures caused the erosion of 430 000 m 3 of sediment in eight years. Abstract: Adopting a multidisciplinary approach, we mapped with unprecedented detail the seafloor morphology, sediment distribution and benthic habitats of a tidal inlet in the Venice Lagoon, Italy, which has been greatly impacted by human activity. Thanks to very high‐resolution multibeam data, we identified ebb and flood‐tidal deltas, a tidal point bar, active dune fields, pools and scour holes. The seafloor substrate of the inlet was investigated by integrating automatically classified multibeam backscatter data with sediment samples and underwater seafloor images. The sediment composition comprises four textural classes with 75% overall thematic accuracy. The particle size distribution of each morphological feature was assessed distinguishing, in particular, sediments over crests and troughs of small‐dune fields with wavelengths and heights of less than 4 m and 0.2 m, respectively. Adopting state‐of‐the‐art benthic habitat mapping procedures, we found seven distinctive benthic habitats that reflect spatial variability in hydrodynamics and sediment transport pathways. The dominant classes were Sand with sparse shell detritus (46%) and Bare sand (32%). The rip‐rap revetment used for the inlet jetties and for the hard structures, built in the inlet channel to protect Venice from flooding, created a new habitat that covers 5.5% of the study area. This study shows how combining geomorphological and ecological analyses is crucial for the monitoring and management of tidal inlets and coastal infrastructures. © 2019 John Wiley & Sons, Ltd.